(untitled) (Nonconventional Technologies Review, 2025)
This research explores the technical viability of utilising Material Extrusion (MEX) Additive Manufacturing (AM) technology for the fabrication of bending devices. The primary objective of this undertaking is to investigate the potential for decreasing production costs and accelerating lead times. The present study builds upon the findings of earlier investigations by means of an examination of the performance of polymer-based devices, which had previously been subjected to finite element analysis (FEA). The method advances the field by using a polymer-based die. The findings suggest that this method has potential application in small-batch production and prototyping, with a consistency between the experimental results and the predictions made via finite element analysis.